Training on the use of digital media for implementation digital pharmacy for pharmacist at Salatiga in supporting the industrial revolution 4.0 - Dian Oktianti; Jaya Ramadey Bangsa; Anita Kumala Hati (Universitas Muhammadiyah Magelang, 2022)
Today, the health sector has begun to adopt digital information technology, one of which is telemedicine. Utilization of digital media can be used for business interests and support pharmaceutical care activities. However, pharmacists in Salatiga city have not been able to make optimal use of digital media. This activity was carried out in the form of training on the use of digital media for the implementation of digital pharmacy for IAI PC Pharmacists in Salatiga City in facing the era of the industrial revolution 4.0. Activities carried out are training and providing information about digital pharmacy and medication therapy management. This program has proven successful in increasing pharmacist knowledge regarding digital pharmacy and medication therapy management with a p-value of 0.0000. Furthermore, 69 pharmacists experienced an increase in knowledge, 5 pharmacists experienced a decrease, and 7 pharmacists did not experience an increase in knowledge.